2015
DOI: 10.1183/13993003.00458-2015
|View full text |Cite
|
Sign up to set email alerts
|

A repeated short educational intervention improves asthma control and quality of life

Abstract: We assessed the effectiveness of an asthma educational programme based on a repeated short intervention (AEP-RSI) to improve asthma control (symptom control and future risk) and quality of life.A total of 230 adults with mild-to-moderate persistent uncontrolled asthma participated in a 1-year cluster randomised controlled multicentre study. The AEP-RSI was given in four face-to-face sessions at 3-month intervals, and included administration of a written personalised action plan and training on inhaler techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 32 publications
3
24
0
5
Order By: Relevance
“…FU: 12 moI groups had fewer unscheduled visits [I: 0.8 (SD 1.4) and I s : 0.3 (SD 0.7) vs. C:1.3 (SD 1.7); p  = 0.001], and greater improvements in asthma control ( p  = 0.042) and QoL ( p  = 0.019).Rice 2015 [66]711 participantsPAAP + inpatient lay educator vs. PAAP.Components: Inpatient lay educatorEncourage FU attendance, build self-efficacy, set goals, overcome barriers.Children 2–17 y admitted with asthma.RCT.FU: 1 moNo difference in attendance at FU appointment. I group had greater preventer use (OR 2.4, 95% CI 1.3–4.2), PAAP ownership (OR 2.0, 95% CI 1.3–3.0) and improved self-efficacy ( p  = 0.04).Yeh 2016 [67]76 participantsFamily programme (+PAAP) vs. usual care (+PAAP).Components: Family empowermentFamily empowerment to reduce parental stress, increase family functioning.Children 6–12 y with asthma.RCT.FU: 3 moI families had reduced parental stress index ( p  = 0.026) and improved family environment scores ( p  < 0.0001), improved lung function, less disturbed sleep, less cough but no difference in wheeze.Zairina 2016 [68]72 participantsTelehealth supported PAAP vs. usual care.Components: TelehealthTelehealth (FEV 1 , symptoms) monitored weekly.Pregnant women with moderate/severe asthmaRCT.FU: 6 moTelehealth improved ACQ [MD 0.36 (SD 0.15, 95% CI −0.66 to −0.07)] and mAQLQ [MD 0.72 (SD 0.22; 95% CI 0.29–1.16)].No difference in perinatal outcomes. Abbreviations : ACQ Asthma Control Questionnaire, AQLQ Asthma Quality Of Life Questionnaire, C control, CI confidence interval, FEV 1 forced expiratory volume in one second, FU follow-up, I intervention, LTC long-term condition, mAQAL mini Asthma Quality Of Life Questionnaire, MD mean difference, mo month, OR odds ratio, PAAP personalised asthma action plan, QoL quality of life, RCT randomised controlled trial, SD standard deviation, SMD standardised mean difference, y year …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FU: 12 moI groups had fewer unscheduled visits [I: 0.8 (SD 1.4) and I s : 0.3 (SD 0.7) vs. C:1.3 (SD 1.7); p  = 0.001], and greater improvements in asthma control ( p  = 0.042) and QoL ( p  = 0.019).Rice 2015 [66]711 participantsPAAP + inpatient lay educator vs. PAAP.Components: Inpatient lay educatorEncourage FU attendance, build self-efficacy, set goals, overcome barriers.Children 2–17 y admitted with asthma.RCT.FU: 1 moNo difference in attendance at FU appointment. I group had greater preventer use (OR 2.4, 95% CI 1.3–4.2), PAAP ownership (OR 2.0, 95% CI 1.3–3.0) and improved self-efficacy ( p  = 0.04).Yeh 2016 [67]76 participantsFamily programme (+PAAP) vs. usual care (+PAAP).Components: Family empowermentFamily empowerment to reduce parental stress, increase family functioning.Children 6–12 y with asthma.RCT.FU: 3 moI families had reduced parental stress index ( p  = 0.026) and improved family environment scores ( p  < 0.0001), improved lung function, less disturbed sleep, less cough but no difference in wheeze.Zairina 2016 [68]72 participantsTelehealth supported PAAP vs. usual care.Components: TelehealthTelehealth (FEV 1 , symptoms) monitored weekly.Pregnant women with moderate/severe asthmaRCT.FU: 6 moTelehealth improved ACQ [MD 0.36 (SD 0.15, 95% CI −0.66 to −0.07)] and mAQLQ [MD 0.72 (SD 0.22; 95% CI 0.29–1.16)].No difference in perinatal outcomes. Abbreviations : ACQ Asthma Control Questionnaire, AQLQ Asthma Quality Of Life Questionnaire, C control, CI confidence interval, FEV 1 forced expiratory volume in one second, FU follow-up, I intervention, LTC long-term condition, mAQAL mini Asthma Quality Of Life Questionnaire, MD mean difference, mo month, OR odds ratio, PAAP personalised asthma action plan, QoL quality of life, RCT randomised controlled trial, SD standard deviation, SMD standardised mean difference, y year …”
Section: Resultsmentioning
confidence: 99%
“…Generic parenting skills initiatives improved self-efficacy in families struggling to manage young children with asthma, with inconsistent effect on asthma outcomes [64, 67]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that education in self-management of asthma with symptom or peak flow monitoring, combined with regular medical visits and written action plans, is effective in improving health outcomes in adults with asthma 25,26. In a 1-year cluster randomized controlled multicenter study with the participation of 230 adults with mild-to-moderate persistent uncontrolled asthma, an asthma educational program based on a repeated short intervention, given in four face-to-face sessions at 3-month intervals was effective in improving asthma symptom control, future risk, and quality of life 27. In this study, the education program included administration of a written personalized action plan and training on inhaler technique 27.…”
Section: Difficult-to-control Asthmamentioning
confidence: 99%
“…In a 1-year cluster randomized controlled multicenter study with the participation of 230 adults with mild-to-moderate persistent uncontrolled asthma, an asthma educational program based on a repeated short intervention, given in four face-to-face sessions at 3-month intervals was effective in improving asthma symptom control, future risk, and quality of life 27. In this study, the education program included administration of a written personalized action plan and training on inhaler technique 27. Other experiences reported similar results.…”
Section: Difficult-to-control Asthmamentioning
confidence: 99%
“…The study by PLAZA et al [27] suggests that "simplified" educational interventions can be effective if they offer the essential elements of an effective educational intervention, such as key information on asthma management, provision of a personalised but easy to understand action plan, and inhaler technique training [4,8,31,32]. The study's success may also be partly explained by the repetition of key messages at regular intervals over a 1-year period, the three components of the education programme being checked at each encounter, and the establishment of individualised goals for each patient [32].…”
mentioning
confidence: 99%